Terminology related to so-called deductions from remuneration for work. Gloss to the judgment of the Polish Supreme Court of March 8, 2023, I PSKP 32/22 - Liskowski, Mariusz (Studia Iuridica Toruniensia, 2025)
This gloss is devoted to the problem of nomenclature related to the so-called deductions from remuneration for work. The author presents the judgment of the Supreme Court and the facts of the case, based on which the commented judgment was issued. In principle, he approves the position taken by the Supreme Court. However, he questions the terminology used in the thesis of the judgment under review. This is because the law does not contain a legal definition – “deduction from remuneration for work”. The commented judgment also does not define this term. At the same time, the Supreme Court, in the thesis of the judgment under review, used the phrase “deductions” referring to remuneration for work. The analysis of the legislation led the glossator to the conclusion that the Supreme Court used the analysed term not in a legal, but in a lexical or juridical sense.